2010
DOI: 10.1186/1479-5868-7-55
|View full text |Cite
|
Sign up to set email alerts
|

Maternal feeding practices, child eating behaviour and body mass index in preschool-aged children: a prospective analysis

Abstract: BackgroundPrevious research has found associations between parental feeding practices and children's eating behaviour and weight status. Prospective research is needed to elucidate these relationships.MethodsOne hundred and fifty-six mothers of 2- to 4-year-old children completed questionnaires including measures of maternal feeding practices (pressure to eat, restriction, monitoring and modelling of healthy eating), child eating behaviour (food responsiveness, food fussiness and interest in food), and mother … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
163
6
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(190 citation statements)
references
References 41 publications
16
163
6
5
Order By: Relevance
“…However, it is striking that parent-report measures of pressure to eat are associated with lower (rather than higher) weight, in both cross-sectional (Ventura & Birch, 2008) and longitudinal (Farrow & Blissett, 2008) studies. Longitudinal studies by Gregory et al have additionally found that pressure to eat predicts lower interest in food and greater food fussiness in children (Gregory et al, 2010a), and less fruit intake, even when controlling for initial intake (Gregory et al, 2011). These studies could refl ect pressure causing low weight and unhealthy eating behaviour, but even the longitudinal results do not rule out the possibility that pressure simply tracks children ' s eating behaviour and weight.…”
Section: Pressure To Eatmentioning
confidence: 84%
“…However, it is striking that parent-report measures of pressure to eat are associated with lower (rather than higher) weight, in both cross-sectional (Ventura & Birch, 2008) and longitudinal (Farrow & Blissett, 2008) studies. Longitudinal studies by Gregory et al have additionally found that pressure to eat predicts lower interest in food and greater food fussiness in children (Gregory et al, 2010a), and less fruit intake, even when controlling for initial intake (Gregory et al, 2011). These studies could refl ect pressure causing low weight and unhealthy eating behaviour, but even the longitudinal results do not rule out the possibility that pressure simply tracks children ' s eating behaviour and weight.…”
Section: Pressure To Eatmentioning
confidence: 84%
“…Maladaptive feeding practices often derive from a parent's anxiety about the health and wellbeing of their child; the belief that their child is unable to selfregulate (Tan & Holub, 2011), is perceived to be underweight (Galloway et al, 2006) or overweight (Gregory, Paxton, & Brozovic, 2010a), or over responsive to food (Gregory, Paxton, & Brozovic, 2010b and/or when children's patterns of acceptance and rejection are not consistent with requirements for a balanced diet and healthy weight and growth (Dennison, 1996;Fisher & Kral, 2008;Pugliese et al, 1987), interventions are required which provide the necessary information and support to address this discrepancy.…”
Section: Parent-focussed Interventions For Non-clinical Feeding Diffimentioning
confidence: 99%
“…Untuk perilaku enjoyment of food, umumnya mulai meningkat di usia 12 bulan dan terjadi penurunan di usia 5-6 tahun (16,23,25). Berdasarkan beberapa penelitian, perbedaan perilaku makan setiap anak dipengaruhi oleh faktor genetik, perilaku pemberian makan, pola asuh, perilaku makan orangtua, dan lingkungan obesogenik (26)(27)(28)(29)(30)(31).…”
Section: Bahasanunclassified
“…Faktor genetik diketahui dapat memengaruhi perilaku makan pada anak, khususnya gen FTO (Fat mass obesity) yang berperan dalam mengontrol asupan makanan dan pilihan makanan (16,24,31). Selain itu, perilaku orangtua juga dapat memengaruhi perilaku makan anak yaitu melalui perilaku pemberian makan, dan perilaku makan orangtua (27,28,30,(35)(36)(37)(38).…”
Section: Bahasanunclassified